Ex Vivo Comparison of the Accuracy of a Clamped with a Hand-Held Drill Guide for Drilling Distal Third Metacarpals and Metatarsals in Equids - James, Oliver A.; Elce, Yvonne; Cillán-Garcia, Eugenio; Reardon, Richard J.M. (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objectives The aim of this study was to determine whether a clamped drill guide can be used effectively to drill across equine distal third metacarpals and metatarsals and to compare accuracy and speed of a drilling with a hand-held drill guide.Study Design Eighty equine cadaver limbs were divided between four surgeons with varying experience. The limbs were randomly allocated to clamped or hand-held drill guides and placed in a stand in an upright/standing position on a metal table. Drilling times from cis- to trans cortices were measured. Post-drilling computed tomography images were used to assess drilling deviations in the dorsopalmar and proximodistal directions.Results Mean proximodistal deviation of the drill hole was distad for both guides and significantly (p = 0.01) less for the clamped drill guide +0.35° (range: –5.42°, +6.61°, standard deviation [SD] ± 3.18°) than the hand-held drill guide +2.05° (range: –5.24°, +9.81°, SD ± 3.69°). Mean dorsopalmar/plantar deviation was non-significantly (p = 0.17) less for the clamped drill guide −0.27° (range: −9.72°, +6.58°, SD ± 3.57°) than the hand-held drill guide +0.60° (range: −9.74°, + 12.33°, SD ± 4.51°). Mean time taken to drill from cis to trans cortex was significantly (p < 0.001) shorter with the clamped drill guide (41.2s) than the hand-held guide (56.6s).Conclusion The clamped drill guide could be used successfully on the equine distal third metacarpals and metatarsals and resulted in some improved accuracy and reduced drilling time compared with the hand-held guide. The use of the clamped drill guide in vivo could be supported. This may be of benefit for certain fracture repairs in equids.
Keywords: fracture; drill guide; hole drilling accuracy; metacarpal; metatarsal